Comparison between some of the variables of biomechanics using forehand (the forward and top spin) for advanced tennis players - Mohammed Saeed, Bilal Kh. (Humanities Journal of University of Zakho, 2014)
The idea behind the study is an attempt to compare some of the mechanical forehand (the forward and top spin) to get to any of the two forms to perform better according to the base technique motor depending on the analysis kinetic in order to access any of the figures made ​​by the player using less effort to get a result serving game and coaches to identify and then sheds light on it during games.